Expression of eicosanoid receptors subtypes and eosinophilic inflammation: implication on chronic rhinosinusitis - Van Cauwenberge Paul; Claeys Cindy; Pérez-Novo Claudina; Bachert Claus (Respiratory Research, 2006)
Abstract Background Eicosanoid receptors are G-protein-coupled receptors playing an important immunomodulatory role in airway diseases. However, there is little information on the expression of these receptors and their link with eosinophilic inflammation in paranasal sinus diseases. We aimed with this study to investigate the tissue expression of leukotrienes and prostaglandin E2 receptors in chronic rhinosinusitis patients and the link of this regulation with eosinophilic inflammation. Methods Samples were prepared from nasal tissue of patients with chronic rhinosinusitis without nasal polyps (CRS, n = 11), with nasal polyps (CRS-NP, n = 13) and healthy subjects (Controls, n = 6). mRNA expression of CysLT1, CysLT2, BLT1, BLT2, E-prostanoid receptors (EP1, EP2, EP3, EP4) and sol-IL-5Rα was determined by real-time PCR. Concentrations of PGE2, LTC4/D4/E4, LTB4 and sol-IL-5Rα were determined by ELISA and of ECP by ImmunoCap. Protein expression and tissue localization of eicosanoid receptors and activated eosinophils were evaluated by immunohistochemistry. Results CysLT1 mRNA expression was significantly increased in CRS-NP compared to CRS and controls, and CRS compared to controls, whereas CysLT2 mRNA was enhanced in both CRS groups without differences between them. Levels of both receptors correlated to the number of activated eosinophils, sol-IL-5Rα, ECP and LTC4/D4/E4 concentrations in the disease groups. PGE2 protein concentrations and prostanoid receptors EP1 and EP3 were down-regulated in the CRS-NP tissue vs. CRS and controls, whereas EP2 and EP4 expression was enhanced in CRS and CRS-NP patients vs. controls. No differences in BLT receptors were observed between patients and controls. Conclusion CyLTs receptors are up-regulated in nasal polyp tissue and their expression correlate with eosinophilic inflammation supporting previous results. Eicosanoid receptors mRNA pattern observed suggests that down-regulation of EP1 and EP3 in CRS-NP and up-regulation EP2 and EP4 in CRS and CRS-NP groups may have some role in the development of the diseases and their regulation may not be directly linked to eosinophil activation but involve post-transcriptional events mainly related to other inflammatory cell sources.